2019
DOI: 10.1111/jcmm.14083
|View full text |Cite
|
Sign up to set email alerts
|

HPCAL1 promotes glioblastoma proliferation via activation of Wnt/β‐catenin signalling pathway

Abstract: Glioblastoma ( GBM ) is the most prevalent primary malignancy of the central nervous system with obvious aggressiveness, and is associated with poor clinical outcome. Studies have indicated that calcium ion (Ca 2+ ) can positively regulate the initiation of malignancy with regard to GBM by modulating quiescence, proliferation, migration and maintenance. Hippocalcin like‐1 protein ( HPCAL 1) serves as a sensor of Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…In addition, our further research showed that EPS1-1 regulated the expression of oncogenes and tumor suppressor genes, thereby through which might exert its biological function. These genes include cell proliferation promoting factors including CCND1 and c-Myc (Wang G. et al, 2019;Zhang D. et al, 2019), cell apoptosis regulators BAX and Bcl-2 (Zhang Q. et al, 2019;Hu et al, 2020), and factors that promote cell migration and invasion, such as Vimentin and Slug (Lillo Osuna et al, 2019;Shahid et al, 2019). Study by Song et al (2019) showed that EPS1-1 could reduce the expression of oncoproteins such as COX-2, β-catenin, CyclinD1, and C-Myc, and down-regulate the expression of proliferation-related proteins including Ki-67 and PCNA and the anti-apoptotic gene Bcl-2, up-regulate the expression of pro-apoptotic genes such as p53 and Bax, reduce the number of CD68, F4/80, and NF-κB positive cells, as well as reducing the concentrations of inflammatory factors in serum including TNF-α and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our further research showed that EPS1-1 regulated the expression of oncogenes and tumor suppressor genes, thereby through which might exert its biological function. These genes include cell proliferation promoting factors including CCND1 and c-Myc (Wang G. et al, 2019;Zhang D. et al, 2019), cell apoptosis regulators BAX and Bcl-2 (Zhang Q. et al, 2019;Hu et al, 2020), and factors that promote cell migration and invasion, such as Vimentin and Slug (Lillo Osuna et al, 2019;Shahid et al, 2019). Study by Song et al (2019) showed that EPS1-1 could reduce the expression of oncoproteins such as COX-2, β-catenin, CyclinD1, and C-Myc, and down-regulate the expression of proliferation-related proteins including Ki-67 and PCNA and the anti-apoptotic gene Bcl-2, up-regulate the expression of pro-apoptotic genes such as p53 and Bax, reduce the number of CD68, F4/80, and NF-κB positive cells, as well as reducing the concentrations of inflammatory factors in serum including TNF-α and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo signaling pathway that controls animal organ size through cell proliferation and apoptosis regulation, including cell proliferation, apoptosis, and various stress responses [ 103 ], was significantly enriched in the medium and high dose groups (Supplementary Figs. 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aerobic glycolysis inhibits the proliferation of hepatocellular carcinoma (HCC) cells by downregulating ACTG1, and a high level of ACTG1 is significantly related to advanced hepatoma [53]. HPCAL1 increases the proliferation and growth of glioblastoma by activating the Wnt/β-catenin pathway [54]. Yeon et al [55] found that 13.9% of colorectal cancers (CRCs) in 124 patients had ANK3 gene frameshift mutations and intratumoral heterogeneity, and low expression of ANK3 could inhibit detachment-induced apoptosis and promote CRC cell survival.…”
Section: Discussionmentioning
confidence: 99%